Pengendalian Persediaan Bahan Baku Pada UMKM Bolu Pisang Ibu Onih - Alya Assyifa Fajrin; Dian Anggraeni; Sulaeni Sulaeni (Universitas Galuh, 2026)
Inventory control is a crucial aspect of business operations, especially those that use perishable raw materials such as agricultural products. UMKM Bolu Pisang Ibu Onih uses ambon lumut banana as raw materials, which are prone to spoilage. In its operations, this MSME has experienced losses due to excess inventory and spoilage. This study aims to determine the optimal amount of inventory and frequency of ordering ambon lumut banana to minimize losses and improve business efficiency. The method used is a modified Economic Order Quantity (EOQ) model for perishable products (EOQ Perishable), accompanied by Safety Stock (SS) calculations, based on operational data for one year. The results of the study show that with the application of the EOQ model, the optimal inventory quantity is 371 kg per order, the ordering frequency is 91 times per year, and the required safety stock is 285 kg. The application of the EOQ model has been proven to reduce total inventory costs by IDR 3,761,468.